Charge exchange and x-ray emission cross sections for multiply charged ions colliding with H2O - Otranto, Sebastián (2008)
Total and state selective nl-electron capture cross sections are presented for highly charged ions Z=4–10, 14, 18, and 26 colliding with water molecules. The energy range investigated was from 10 eV/amu v =0.02 a.u. to 100 keV/amu v=2 a.u.. An initialization for the 1B1 and 3A1 orbitals of the water molecule is introduced based on the one center expansion of Moccia and compared to our previous studies based on a hydrogenic approximation within the microcanonical ensemble. The Z dependence of the calculated total cross sections is in reasonable agreement with the recent data of Mawhorter et al. Phys. Rev. A 75, 032704 2007 and is improved over previous results. The energy dependence of the n- and l-level populations is investigated. The K-shell x-ray emission cross sections are determined by using the calculated state-selective electron capture results as input and then applying hydrogenic branching and cascading values for the photon emission. Our results compare favorably with experimental data from the KVI-Groningen, Jet Propulsion Laboratory and Lawrence Livermore National Laboratory groups.